2007
DOI: 10.1590/s1516-89132007000300010
|View full text |Cite
|
Sign up to set email alerts
|

Growth and survival of dorado Salminus brasiliensis (Pisces, Characidae) post-larvae cultivated with different types of food and photoperiods

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 19 publications
1
15
0
7
Order By: Relevance
“…This data is in consonance with those found in the first feeding of yamú (Atencio-Garcia et al, 2003) and dourado (Salminus brasiliensis) (Schütz & Nuñer, 2007). These studies verified an improvement of animal development and decreasing of cannibalism by using forage larvae.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This data is in consonance with those found in the first feeding of yamú (Atencio-Garcia et al, 2003) and dourado (Salminus brasiliensis) (Schütz & Nuñer, 2007). These studies verified an improvement of animal development and decreasing of cannibalism by using forage larvae.…”
Section: Resultssupporting
confidence: 90%
“…), which easily reproduce, have also been used as food in larviculture of many fresh water species, being thus considered an excellent food source for initial (growth) phases (Schütz & Nuñer, 2007). Conversely, high costs and difficulty to find adequate products to perform induced fish reproduction has forced farmers to seek for alternative live feedstuff.…”
Section: Introductonmentioning
confidence: 99%
“…In continuation, we are going to focus on the experiments where authors found survival relation with studied environmental parameters. For photoperiod, authors found that species such as Oreochromis niloticus, Seriola lalandi and Salminus brasiliensis reach higher survival rates under continuous light conditions (El-Sayed & Kawanna, 2004), (Stuart & Drawbridge, 2012), (Schütz & Nuñer, 2007 photoperiod and survival. Similar relation was found with Miichthys miiuy, their maximum death rates were related to continuous dark conditions.…”
Section: Discussion On the Effects Of Environmental Parameters On Fishmentioning
confidence: 99%
“…Authors did not find any differences in SGR. Schütz and Nuñer (2007) studied the effect of photoperiod on post-larvae of Salminus brasiliensis. No correlation was found between growth and photoperiod.…”
Section: Effects Of Photoperiodmentioning
confidence: 99%
See 1 more Smart Citation